Antibacterial and Anticancer Activities of Naturally Derived Nano Calcium Carbonate for Biomedical Applications - Thenpandiyan, E.; Ramasamy, V.; Suresh, G.; Senthil, S.; Sathishpriya, T. (Asian Journal of Chemistry, 2025)
Pristine CaCO3 nanoparticles was synthesized through an eco-friendly biomimetic route using a natural calcium carbonate source of CaMg(CO3)2 (dolomite rock). The physico-chemical properties of prepared CaCO3 nanoparticles were assessed using FTIR, XRD, FE-SEM, HR-TEM and XPS analyses. The presence of the functional groups through FTIR analysis confirmed the presence of CaCO3 (calcite polymorph) in the synthesized sample. The occurrence of rhombohedral CaCO3 with a well-crystalline nature was confirmed through XRD pattern and calculated crystallite size is about 25 nm. The FE-SEM and HR-TEM analyses exhibit the spherical with few rhombohedral like morphology. The presence of binding energies of Ca, O and C confirms that the synthesized sample is in the pure form of CaCO3. The biomedical activities of prepared CaCO3 nanoparticles were examined through antibacterial and anticancer activities using Gram-positive (Staphylococcus aureus) and Gram-negative bacteria (Salmonella sp.) and the human breast cancer cell line MCF-7. These results show that CaCO3 nanoparticles act as good antibacterial agents. The cytotoxicity effect of CaCO3 nanoparticles on MCF-7 is 18% cell viability at 1000 µg/mL. The calculated IC50 value of CaCO3 nanoparticles against MCF-7 is 229.10 µg/mL. These results show that the naturally derived CaCO3 nanoparticles are potent anticancer drugs against human breast cancer cell lines.